Population Dynamics and Life Cycle of Teak Defoliator Hyblaea Puera Cramer., (Lepidoptera: Hyblaeidae) in Lao People's Democratic Republic - Vongxomphou, Thansamay (2001)
Forest lands in Lao People's Democratic Republic (Lao P.D.R) are largely owned and administered by the government. Teak (Tectona grandis) is one of the important hardwood species planted extensively in plantation in the northern part of Lao P.D.R for commercial purposes, but teak tree has numerous diseases, and insect pests which cause damage to the teak plantation. Teak defoliator Hyblaea puera is an important pest of teak in Lao P.D.R. It occurs every year during May to July when the tree flushes leaves. This study was conducted in the natural teak forest and teak plantations within two provinces i.e. Xayabury and Luang Prabang. This study investigated the population dynamics and distribution of the insect in different teak plantations, and its life cycle. During a two-year period covering 1999 and 2000, the outbreak season for teak defoliator H puera occurred in early May when the teak developed new leaves,